2015
DOI: 10.4070/kcj.2015.45.2.110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pretreatment of Ezetimibe/Simvastatin on Arterial Healing and Endothelialization after Drug-Eluting Stent Implantation in a Porcine Coronary Restenosis Model

Abstract: Background and ObjectivesWe sought to evaluate the effect of the early use of ezetimibe/simvastatin (Vytorin®) on arterial healing and endothelialization after the implantation of a drug-eluting stent (DES) in a porcine model of coronary restenosis.Materials and MethodsA total of 20 pigs (40 coronary arteries) were randomly allocated to a pretreatment or no treatment group. The pretreatment group (n=20) received oral ezetimibe/simvastatin (10/20 mg) daily for 7 days before stenting and the no pretreatment grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…This late benefit of BP-BES might be attributable to biocompatibility through polymer biodegradation, although the lower risk profile of the BP-BES group compared with the DP-EES group could be another explanation. It was reported that BP-BES showed a strong trend of lower inflammation score and had significantly lower fibrin and injury scores than DP-EES in histopathological assessments 21). Taken together, the possible drawbacks of the thicker strut in BP-BES, which is associated with a higher risk of adverse clinical outcome, might be offset by the advantages of its BP.…”
Section: Discussionmentioning
confidence: 95%
“…This late benefit of BP-BES might be attributable to biocompatibility through polymer biodegradation, although the lower risk profile of the BP-BES group compared with the DP-EES group could be another explanation. It was reported that BP-BES showed a strong trend of lower inflammation score and had significantly lower fibrin and injury scores than DP-EES in histopathological assessments 21). Taken together, the possible drawbacks of the thicker strut in BP-BES, which is associated with a higher risk of adverse clinical outcome, might be offset by the advantages of its BP.…”
Section: Discussionmentioning
confidence: 95%